2011
DOI: 10.1159/000324405
|View full text |Cite
|
Sign up to set email alerts
|

Thyroglossal Duct Cyst Papillary Carcinoma

Abstract: Thyroglossal duct cysts are usually located in the midline of the neck. The coexistence of carcinomas in thyroglossal duct cysts is extremely rare, with most being papillary carcinomas. Usually, the diagnosis is only made postoperatively after excision of the cyst. Although the Sistrunk procedure is often regarded as adequate, controversies exist concerning the need for thyroidectomy depending on histopathological findings. We report the case of a 31-year-old man diagnosed with papillary carcinoma within a thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 10 publications
1
65
0
4
Order By: Relevance
“…8 Their cause is unknown and there are no predisposing factors, i.e., The etiology of the papillary carcinoma arising in a TDC is unclear but, generally, there are two theories which can explain this phenomenon, de novo origin and spread from a primary thyroid gland tumor. 10 Firstly, the de novo theory is based on the fact that in 62% of cases, ectopic thyroid tissue can be identified histopathologically, and this is supported by the absence of a medullary carcinoma in the TGD as it arises from parafollicular cells. 11 The second is the metastatic theory which suggests that thyroglossal cyst carcinoma is the result from metastatic from an occult primary thyroid gland, as papillary carcinoma is multifocal in nature.…”
Section: Discussionmentioning
confidence: 99%
“…8 Their cause is unknown and there are no predisposing factors, i.e., The etiology of the papillary carcinoma arising in a TDC is unclear but, generally, there are two theories which can explain this phenomenon, de novo origin and spread from a primary thyroid gland tumor. 10 Firstly, the de novo theory is based on the fact that in 62% of cases, ectopic thyroid tissue can be identified histopathologically, and this is supported by the absence of a medullary carcinoma in the TGD as it arises from parafollicular cells. 11 The second is the metastatic theory which suggests that thyroglossal cyst carcinoma is the result from metastatic from an occult primary thyroid gland, as papillary carcinoma is multifocal in nature.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that this failure to involute occurs in approximately 7% of the population (11). The etiology of the papillary carcinoma arising in a thyroglossal duct cyst is unclear but, generally, there are two theories which can explain this phenomenon, de novo origin and spread from a primary thyroid gland tumor (12 ). Most authors support the theory of primary de novo origin by the ectopic thyroid nests of the cyst wall rather than the metastatic spread from a primary thyroid gland tumor through the duct from the thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Hirshoren et al [2] in their review of 160 cases of thyroglossal duct cysts, reported papillary carcinoma in only one patient. Total number of reported cases in world literature till date is 275 [3]. Although papillary thyroid carcinoma is the most common type, squamous carcinomas can also occur [4].…”
Section: Introductionmentioning
confidence: 99%